NILAI JASA LINGKUNGAN KAWASAN HUTAN SEBAGAI PENYEDIA AIR BERSIH BAGI MASYARAKAT SEKITAR KAWASAN TAHURA NIPA-NIPA. KOTA KENDARI - Mukaddas, Jamal (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Value of Environmental Services for the Nura-Nipa Tahura Region as a Provider of Clean Water Sources for Communities Around the Tahura Nipa-Nipa Area in Kendari City, This study aims to find out: how much the value of the Tahura Nipa-Nipa Region provides a source of clean water for the people of Watu-Watu Village. This research was conducted in the Tahura Nipa-Nipa area, in the community of users of clean water in the TAHURA Nipa-Nipa area, which took place in October 2018. Primary data is data obtained directly from individual targets individuals such as interview and observation data. Interviews were carried out by filling out questionnaires / questionnaires, while observing by observing activities. Secondary data is data obtained from regional bodies, relevant agencies, local government in the form of notes, books, reports, tables or diagrams about the research area and carried out based on the principle of purposive sampling for location determination and Simple random sampling for determination Respondents by collecting data that have been determined based on simple random sampling, obtained 21 families or 20% (respondents) from 105 households. ased on the results of the observation, it was concluded that the average water use of the Tahura Nipa-Nipa Forest Area in Watu-Watu Subdistrict West Kendari District perKK in one year was 899.66 m3, so with a population of 105 households using clean water from the Tahura Nipa- Forest Area Nipa especially Watu-Watu Village is 944.64 m3. And if the value of the rupiah is calculated based on the current PDAM price for the people of Watu-Watu Village, it ranges from Rp. 472,320,000 / year. While the total willingness to pay the community (Willingness to Pay / WTP) ranges from Rp. 442,251,000, -. This is also due to the different levels of people's livelihoods and the level of willingness of the community to pay for the availability of water from the Tahura Nipa-Nipa Area.